THE IMPORTANCE OF SPORTS GYMNASTICS FOR PHYSICAL TRAINING - Seyitbekova Zulfiya Reyimbek qizi (American Journal of Applied Science and Technology, 2024)
The article talks about the importance of sports gymnastics in training the human body and moving it, and also focuses on the history of its importance.